Selective Synthesis of exo-Spiro[2′,2′-difluorocyclopropane-3′,2′-tropanes] - Gerasov, Andrii; Dolgonos, Grygoriy A.; Mandzhulo, Aleksandr Yu.; Ryabitsky, Alexey; Fetyukhin, Volodymyr; Lukin, Oleg; Shivanyuk, Alexander (Synthesis, 2020)
Conformationally restrained exo-isomers of N-Boc-protected spiro[2′,2′-difluorocyclopropane-3′,2′-tropanes] were synthesized in 62–83% yield via absolutely diastereoselective cycloaddition of CF2, generated in situ from Me3SiCF3/NaI in refluxing THF, to double bonds of 3-alkylidenetropanes. Standard removal of Boc protecting groups afforded corresponding exo-spiro[2′,2′-difluorocyclopropane-3′,2′-tropane] hydrochlorides in 82–94% yields. DFT and CCSD(T) calculations revealed that the observed exo-selectivity of difluorocarbene addition is likely to be caused by a lower activation barrier of the exo-difluorocyclopropanation compared to the endo-reaction.
Keywords: tropane; difluorocarbene; diastereoselective difluorocyclopropanation; DFT; CCSD(T)